Kekacauan Perjuangan Subaltern dalam Novel Babad Kopi Parahyangan Karya Evi Sri Rezeki (Pascakolonial Gayatri C. Spivak) - Yusril Ihza Fauzul Azhim (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
The development of the coffee commodity has grown into the literary area. The novel Babad Kopi Parahyangan by Evi Sri Rezeki discusses the long history of colonialism in the plantation sector and the Indonesian coffee industry. This novel also builds on the idea of nationalism in fighting for the rights of farmers and women. This study aims to explain the subaltern struggle according to Gayatri C. Spivak's view. Subaltern is known as a peripheral subject whose voice is always represented, so that their existence is part of the domination practice. This research uses library and note-taking methods to make it easier to understand and analyze the problems in the novel. The result of this research is to review the production chaos of the discourse of subaltern society struggle in the novel as a bourgeois nationalist chain of power. So that in placing the position of struggle, the ideology of the novel is still attached to the traditional values of colonial heritage.